Competency In Critical Care Nursing With Approach Methods Journal Sharing of Critical Care (JSCC) In Nursing Profession Students - Suwardianto, Heru; Astuti, Vitaria Wahyu (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The results showed that most respondents had good critical nursing competency scores including primary assessment: airway assessment (53.8%); breathing assessment (56.4%); Circulation assessment (61.5%); Disability assessment (56.4%); and Exposure assessment (59%), professionalism (56.4%), critical nursing care competencies (79.5%), Clinical reasoning process (71.8%), Patient safety (61.5%) and critical care exam score (46.2%). The result of statistical test with Pearson test obtained that the primary assessment: airway assessment (ρ = 0.038); circulation assessment (ρ = 0.029); Exposure assessment (ρ = 0.023), competence of critical nursing care (ρ = 0.049), clinical reasoning process (ρ = 0.028) and patient safety (ρ = 0.001) have a significant relationship to the critical care exam score. The implementation of learning methods for journal sharing of critical care has a positive impact on competencies and results in good student competencies.